Estudio de satisfacción de usuarios en la red de Bibliotecas del Instituto Cervantes - Martín-montalvo, Irene (Revista General de Información y Documentación, 2008)
It presents a study about the users satisfaction made in July 2006 in order to provide qualitative data for the elaboration of the Plan Director de la Red de Bibliotecas del Instituto Cervantes. The article summarises the used methodology and the analysis of the most relevant results, their possible causes and consequences. The annex includes the survey used for the study.